TOURISM AND THE ROLE OF MUSEUMS IN IT - Yuldasheva Xusniya Kadirjanovna; Najimitdinova Nilufar Nazirovna; Qudratova Dilnoza Hasanovna (Academia Science Repository, 2023)
Tourism (French: our — walk, trip), tourism — travel (trip); one of the types of active recreation. Tourism is defined as the departure (travel) of a natural person from the place of permanent residence for a period of at least 1 year without engaging in paid activities in the destination (country) for health, educational, professional or other purposes. The history of tourism dates back to the beginning of the 19th century. First, organized tourism from England to France was established (1815). The English priest Thomas Cook, who is considered the founder of tourism, organized the first railway tour in 1843. After that, he established his own tour company and in 1866 the first tour groups were sent to the United States. In the East, Ibn Battuta, an Arab traveler, started his journey at the age of 21 and traveled almost all the countries of East and North Africa on foot.